LANGERHANS CELL HISTIOCYTOSIS - Nishimori, Fátima Satomi (2014)
The authors report a case of a young male patient who presented with erythematous and descamative lesions, with maceration, in the axillary and inguinal region, associated with erythematous ulcerated plaques in the perianal region. Histopathological examination was compatible with Langerhans cell histiocytosis, with immunohistochemical positivity for CD1a and S100, thus confirming the diagnosis. Systemic investigation revealed an extra-axial mass in supra-sellar region; he underwent chemotherapy, with a significant improvement of the cutaneous lesions. He keeps his follow-up by the Dermatology, Hematology and Endocrinology Units.